Design and Mechanical Analyses of Mobile Robot with Swerve Driving System - Mısır, Oğuz; Beyazlı, Melike; Alp, Sümeyye; Taşkın, Görkem Burak; Işık, Zeynep (My University, 2024)
The use of mobile robots has become increasingly prevalent in a variety of sectors including industry, healthcare, logistics, and services. Among the most crucial attributes of these robots for their intended applications is their capacity to transport payloads. Autonomous mobile vehicles that are capable of carrying payloads are robots that process the data received from their environment through the electronic components. They contain and deliver the load to the target location in accordance with this data. This study presents the design of a mobile robot with a scissor lift system and a swerve driving system. Finite element analysis is employed to investigate the stress and deformation behavior of the designed vehicle under load. The suitability of the materials used for the design is then checked as a result of the analyses. Following this, the ability of the real-time driving algorithms to act in possible scenarios is tested in a simulation environment.
Keywords: Finite element analysis; Mobile robot; Autonomous